Odpowiedzi

Najlepsza Odpowiedź!
2009-11-26T15:47:23+01:00
A)(x+2y)² +(2x-y)² -5(x-y)(x+y) = x²+4xy+4y²+4x²-4xy+y²-5x²+5y² = 10y²
10*(0,1)² = 10*0,01 = 0,1

b)3y(3y-2x)-(3-x)(x+3)-(x-3y)² = 9y²-6xy-(3x+9-x²-3x) - (x²-6xy+9y²) = 9y²-6xy-9+x²-x²+6xy-9y² = -9


A jeśli od razu podstawiać bez przekształcania to będzie tak:
a) ((-1)+2*0,1)² +(2*(-1)-0,1)² -5((-1)-0,1)((-1)+0,1) = (-1+0,2)²+(-2-0,1)²-5*(-1,1)*(-0,9) = (-0,8)²+(-2,1)²-4,95 = 0,64+4,41-4,95 = 0,1

b) 3*0,1*(3*0,1-2*(-1))-(3-(-1))*((-1)+3)-((-1)-3*0,1)² = 0,3*(2,3)-4*2-(-1,3)² = 0,69-8-(1,69) = 0,69-8-1,69 = -9

1 5 1
2009-11-26T15:54:31+01:00
A)(x+2y)² +(2x-y)² -5(x-y)(x+y) = x²+4xy+4y²+4x²-4xy+y²-5x²+5y² =
10y²

10*(0,1)² = 10*0,01 = 0,1

b)3y(3y-2x)-(3-x)(x+3)-(x-3y)² = 9y²-6xy-9+x² -x²+6xy-9y² = -9
1 5 1